Characteristics and outcomes of acute heart failure in sub Saharan Africa - Sani, Mahmoud Umar (Department of Medicine, 2017)
The main objective of this thesis was to study the clinical characteristics and short-term (6 months) outcome of acute heart failure as well as determine the role of conventional biomarker BNP and the novel biomarker Gal3 in the prognostication of acute heart failure patients. To achieve this, we investigated in the first cohort; 1) the demographic and clinical characteristic of patients with AHF, 2) their echocardiographic parameters and how they predict outcome, 3) the predictors of readmission and mortality, 4) the prevalence and impact of renal dysfunction on AHF and 5) the electrocardiographic pattern in AHF. The outcome measures were worsening renal function (WRF), length of hospital stay, HF readmissions and cardiovascular death within 60 days and all cause, cardiovascular or HF death through 180 days. In the second cohort, we investigated the demographics, clinical characteristics as well as the relationship between plasma levels of BNP and galectin 3 and outcomes (cardiovascular (CV) death or HF hospitalization through week 24) as well as the relationship between the plasma levels of BNP and Gal3 and both left ventricular (LV) and right ventricular (RV) remodeling in patients with AHF.